Narration of Pre-Islamic Poetry and its Sources - Mohd. Shamsuddin, Salahuddin (Advances in Social Sciences Research Journal, 2022)
There is no doubt that the Arabs were illiterate, and they did not depend on the writing, but rather on the oral narrations since the pre-Islamic era. Oral narration in the pre-Islamic era was a technical school in which the young or novice poets learn the principles of poetry, just as the artisans today learn the principles of the craft and the rules of the profession. The junior remains attached to his teacher, carrying out his directions and corrections, and sticking to him as a beneficiary to be able to say and stand out in it, and whoever wanted to learn poetry or be a poet had to commit one of the great poets who was known and recognized for his status, in order to memorize, narrate and excel so that he can get the benefit and proficiency both. The series of narration of pre-Islamic poetry was not interrupted until the era of codification. However, the Orientalist Lyle confirms that who refer to (Muʻallaqāt): Pendants, for example, find that each has its own distinct personality, which proves that it belongs to its owner. Aim of this article is to shed light on that the Pre-Islamic poetry has reached us through the oral narrations, and to respond to those orientalists who doubt the authenticity of those narrations and the narrators who transmitted them until they were codified in the era of codification. In this study, we used the descriptive and historical approach, which is always useful in studying such heretical texts.